TOPÁZIO IMPERIAL DAS MINAS DO VERMELHÃO E JJC, OURO PRETO, MG: ESTUDOS DE INCLUSÕES FLUIDAS E CONSIDERAÇÕES GENÉTICAS - Almeida, A. C. S.; Bello, R. M. S.; Gandini, A. L. (Geochimica Brasiliensis, 2012)